2016
DOI: 10.3390/rel7080101
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Perceptions and Practices of Nursing Students Regarding Spirituality and Spiritual Care

Abstract: Abstract:The aim of this research was to determine Turkish nursing students' knowledge, practices and perceptions of spirituality and spiritual care and to investigate the relationship between their perceptions and their demographics. This study was a descriptive survey conducted at a nursing school providing degree-level education in the city of Manisa, in the western part of Turkey. The sample of the study consisted of the 400 nursing students. A nursing student sociodemographic form, a form on nursing stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 31 publications
2
23
0
3
Order By: Relevance
“…In this study, 54.3% of the participants said that they did not receive education about spirituality, 53.2% said that they did not find enough training on spirituality and spiritual care, and 36% of the participants received this training from the church, mosque, synagogue, etc. The results of the studies carried out in the literature are similar to the results of this study (Kalkim et al 2016;Çelik and Akhan 2016;Midilli et al 2017;Lopez et al 2015;Lovanio and Wallace 2007;Wu et al 2012).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, 54.3% of the participants said that they did not receive education about spirituality, 53.2% said that they did not find enough training on spirituality and spiritual care, and 36% of the participants received this training from the church, mosque, synagogue, etc. The results of the studies carried out in the literature are similar to the results of this study (Kalkim et al 2016;Çelik and Akhan 2016;Midilli et al 2017;Lopez et al 2015;Lovanio and Wallace 2007;Wu et al 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Health professionals who work full-time in the health system have a responsibility to be aware of their patients' spiritual needs and to be sensitive in order to perform psychosocial care, which is an important part of care. However, the majority of health workers have difficulty in evaluating the spiritual aspect of individuals/patients due to lack of information about spiritual care, less time for spiritual care, lack of self-esteem, and multiple work places (Kalkim et al 2016). It is imperative that the knowledge, skills, and attitudes of healthcare professionals are at the professional level.…”
Section: Introductionmentioning
confidence: 99%
“…One study on nurses in India found that spirituality was an important part of dignified dying and meeting the patient's spiritual needs in their end-of-life care was necessary for a dignified death. 34 In the literature, nursing students stated that spiritual care was necessary, 35 although they also stated that they were inadequate in terms of spiritual care 10,25,35 and providing a good death 28,29 Note: Bold value indicates statistically statistical significance P < .05. Abbreviations: ASAPDD, assessment scale of attitudes towards the principles of dying with dignity; SSPS, spiritual support perception scale.…”
Section: Discussionmentioning
confidence: 99%
“…8 Studies have found that nurses and midwives do not have sufficient information about spirituality and spiritual care, and that the information and practices within this field require development. [9][10][11] Therefore, nurses working in health care teams and prospective nursing students should be provided with comprehensive information about spiritual needs, so they that can develop relevant skills and caring methods. Nurses should also be aware that they should plan their patients' care after considering their spiritual values, as this falls within the scope of the spiritual aspect of holistic care.…”
Section: Introductionmentioning
confidence: 99%
“…Once educated via a self-study program, nurses and nursing students revealed changes in their attitude towards spiritual care, but nursing students were more willing to communicate with patients in spiritual distress than nurses [48]. Nursing students expect teachers to help them develop the skills to provide spiritual care [49,50], and no doubts should remain whether spirituality should be taught [12,48]. Indeed, a significant difference in the knowledge and attitudes toward spirituality of nursing students was reported as a result of the integration of spirituality into the undergraduate nursing curriculum [51].…”
Section: Discussionmentioning
confidence: 99%